Helix dynamics in a membrane transport protein: comparative simulations of the glycerol-3-phosphate transporter and its constituent helices. - D'Rozario, R; Sansom, MS (2008)
The glycerol-3-phosphate transporter (GlpT) is a member of the major facilitator superfamily (MFS). GlpT is an organic phosphate/inorganic phosphate antiporter. It shares a similar fold with other MFS transporters (e.g. LacY and EmrD) consisting of 12 transmembrane (TM) helices which form two domains (each of six TM helices) surrounding a central ligand-binding cavity. The TM helices (especially the cavity-lining helices) contain a large number of proline and glycine residues, which may aid in the conformational changes believed to underline the transport mechanism. Molecular dynamics simulations in a phospholipid bilayer have been used to compare the conformational properties of the isolated TM helices with those in the intact GlpT protein. Analysis of these simulations focuses on the role of proline-induced flexibility in the TM helices. Our results are consistent with the proposed rocker switch mechanism for transport by GlpT. In particular, the simulations highlight the cavity-lining helices (H4, H5, H10 and H11) as being significantly flexible, suggesting that the transport mechanism may involve intra-helix motions in addition to pseudo-rigid body motions of the N- and C-terminal domains relative to one another.